Synthesis and physicochemical characterisation of amine functionalised SiO2 /PBI derivatives nanocomposite membrane - Amir Aiman Tahrim; Indok Nurul Hasyimah Mohd Amin (Penerbit Universiti Kebangsaan Malaysia, 2020)
In this study, a series of amine functionalised silica/OPBI nanocomposite membrane for high-temperature polymer electrolyte fuel cell (HT – PEMFC) application were prepared. In order to provide a better dispersion and improving the interfacial interaction between organic/inorganic materials, polyethyleneimine was immobilised onto the surface of silica before added into poly(4,4’-diphenylether – 5, 5’-bibenzimidazole) (OPBI). Nuclear Magnetic Resonance (NMR) experiment proved the synthesised polymer while Fourier-transform infrared spectroscopy (FTIR) and EDX method used to validate the grafting of the amine derivative to the surface of silica in the polymer matrix. Although a satisfactory dispersion pattern was found on all nanocomposite membrane under scanning electron microscope (SEM) studies, agglomeration pattern was seen at higher loading of functionalised silica nanoparticles. The physicochemical characteristic of the nanocomposite membrane was investigated by using thermogravimetric analysis for high temperature PEMFC application. Lower water uptake and swelling ratio in both water and phosphoric acid (PA) showed by the OPBI / SiPEI with an increasing trend as the amount of SiPEI were increased. Addition of amine functionalised silica into OPBI shows a significant improvement compared to pure OPBI while the thermal stability of the membrane at high temperature region (100 – 200 °C) can be influenced by the loading concentration of the amine functionalised silica.